Towards high-resolution X-ray scattering as a probe of electron correlation - Moreno Carrascosa, A; Coe, JP; Simmermacher, M; Paterson, MJ; Kirrander, A (Royal Society of Chemistry, 2022)
X-ray scattering cross sections are calculated using a range of increasingly correlated methods: Hartree–Fock (HF), complete active space self-consistent field (CASSCF), Monte Carlo configuration interaction (MCCI), and full configuration interaction (FCI). Even for the seemingly straightforward case of ground state Ne, the accuracy of the total scattering is significantly better with a more correlated wavefunction. Scanning the bond distance in ground state CO shows that the total scattering signal tracks the multireference character. We examine the convergence of the elastic, inelastic, and total scattering of O3. Overall, the inelastic and total components are found to be the most sensitive to the strength of correlation. Our results suggest that highly accurate measurement of X-ray scattering could provide a sensitive probe of pair-wise correlation between electrons.